Faktor Yang Mempengaruhi Kinerja Keuangan Perusahaan Manufaktur Di BEI Tahun 2016-2018 - Veronika, Elizabeth Sugiarto Dermawan (Fakultas Ekonomi, Universitas Tarumanagara, 2021)
This study aims to analyze and obtain empirical evidence about the effect of managerial ownership, institutional, financial leverage, and firm size on financial performance of manufacture companies listed in the Indonesia Stock Exchange in the period of 2016-2018. The sample selection technique used in this study is purposive sampling method. This study uses secondary data from corporate financial statements from 36 manufacturing companies listed on the Indonesia Stock Exchange during the study period. Data analysis techniques using multiple linear regression with SPSS (Statistical Package for Social Science) for windows version 23.The results indicate that, managerial ownership and firm size have significant effect on financial performance, but institutional ownership and financial leverage do not have an effect significant impact on financial performance.